Early Gallbladder Carcinoma: Demographic Characteristics, Associated Factors and Outcome after Surgery of 40 cases, managed in BIRDEM and Other Tertiary Care Centers of Bangladesh - Muhammad Rafiqul Hassan; Razia Sultana; AHM Tanvir Ahmed; Mirza Shamsul Arefin; Hossain Mohammad Sabbir Raihan; Md Mamunur Rashid (Bangladesh Critical Care Journal, 2025)
Background: Gall bladder carcinoma is the most prevalent biliary tract malignancy worldwide. It has no specific symptoms. Symptoms begin with the advancement of disease and it terminate the life quickly. Thus, early diagnosis and treatment brings good outcome after surgery. Method: This was a cross sectional descriptive study was conducted in admitted patients , in the Department of Hepato-Biliary-Pancreatic surgery and Liver Transplant (HBPS &LTX) in BIRDEM General Hospital , Ibn Sina Specialized hospital and Crescent Gastro Liver and General hospital in Dhaka , over a period of 2 and 1/2 years , from January 2022 to June 2024 . 90% data obtained from BIRDEM and 10% from above mentioned hospitals. An estimated sample size was 86. But due to limitation of time, a total 40 cases had been taken, after considering the inclusions and exclusions criteria. All histopathologically proven early gallbladder carcinoma were included while carcinoma with features of advance malignancy were excluded. Cases were selected irrespective of age, sex, anatomical distribution, clinical presentations, risk factors, histological type and outcome after surgery. Having obtained ethical clearance from the Ethical committee and verbal consent from the the patients, data were collected from the patients, through face to face interview by using a set questionnaire devised for the study by researcher himself. Result: A total 40 cases were included in the study. The peak incidence of gallbladder carcinoma was observed in 5th and 6th decades of life with the mean age of the cases being 58.12±7.75 (range: 35-80) years . Male to female predominance was 1:2.34. Gall stone (80%) was the most common associated factor and mostly diagnosed incidentally in 36 (92.5%) patients. Mostly performed procedure was laparoscopic cholecystectomy and it was about 90% .Tumor involve fundus of the gallbladder in 55% cases and most of these were adenocarcinoma (90%). After surgery wound infection rate 7.5%, port site hernia 5%, there was no recurrence and survivability was 97.5% within this 2 and 1/2 years of study periods. Conclusion: Early surgical intervention brings good result in the management of early gallbladder carcinoma. Bangladesh Crit Care J March 2025; 13 (1): 18-22